Genetic control of resistance to trypanosomiasis - Kemp, Stephen J.; Darvasi, A.; Soller, M.; Teale, A.J. (Elsevier, 1996)
To map the genetic sources of trypanotolerance in mice, a linkage analysis of survival following trypanosome challenge was performed by selective genotyping in a large F2 population produced by crossing the resistant C57BL/6 and susceptible BALB/c inbred mouse lines. We report evidence of a chromosomal region of large effect, possibly comprising more than one resistance locus, on Chromosome 17; and of further loci on Chromosomes 1 and 5. Together, these genes can account for all of the difference between the mean parental phenotypes.